THE BIBLE'S VIEWPOINT (Academia Science Repository, 2023)
This article focuses on the artistic expression of the word " Grief " in the poetry of the People's Republic of Uzbekistan Abdulla Oripov. Behind this topic are discussions about the artistic ideas and ideas that the poet has put forward. Conclusions about the artistic skills of the poet will be given.